KONSUMSI, KECERNAAN NEUTRAL DETERGENT FIBER, DAN ACID DETERGENT FIBER RANSUM YANG MENGANDUNG KULIT BUAH KAKAO (Theobroma cacao L.) TERFERMENTASI PADA KAMBING BLIGON - , EMMA KHOIRUNNISA; , Ir. Subur Priyono Sasmito Budhi, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims were to determine the consumption of Bligon goat fed diet containing fermented cocoa pod and to determine the digestibility of acid detergent fiber (ADF) and neutral detergent fiber (NDF) of diet containing cocoa pod. Twelve 1.5 to 2 year old male Bligon goats were divided into two dietary treatments: P0 (without fermented cocoa pod) and P1 (with 40% fermented cocoa pod). All goats went through 15 days adaptation period,7 days of collection period, and then continued with sample preparation, proximate and Van Soest analysis. The observation parameter included digestibility and nutrient consumption as well as digestibility of NDF and ADF. Results showed that there were no significant differences on NDF and ADF consumption between P0 and P1. Lower NDF and ADF digestibilities were detected on P1 compared with P0 (77,48 vs. 87,14% and 73,18 vs. 86,13%, respectively). It can be concluded that fermented cocoa pod can be used as substitute for grass since no negative effects were shown on NDF and ADF digestibilities.